The development of a DNA vaccine for the Spring Viraemia of Carp Virus (SVCV) - KANELLOS (Θ.Σ. ΚΑΝΕΛΛΟΣ) Th. S; XYLOURI (Ε.Μ. ΞΥΛΟΥΡΗ) E. M.; RUSSEL, P. H. (Journal of the Hellenic Veterinary Medical Society, 2017)
DNA immunization is a promising approach to induce immunity/protection against infectious agents. In the present study a DNA vaccine to Spring Viraemia of Carp Virus (SVCV) G glycoprotein was investigated. The G gene was cloned intact with several promoters namely: 1) the immediate early promoter/enhancer of the human cytomegalovirus; 2) the simian virus 40 promoter; and 3) the porcine myosin heavy chain IIA promoter. In fusion constructs, the G gene was fused either upstream to the LacZ gene or downstream to the murine Ig k-chain leader sequence. BALB/c mice immunized with the aforementioned plasmids produced strong T-cell proliferative responses to the SVCV, in the absence of any detectable antibody response. The group that responded most robusdy was the one that had received the LacZ fusion gene and therefore, this construct was further tested in mice with the addition of a plasmid expressing the murine cytokine GMCSF. Co-administration of the GMCSF expressing plasmid resulted in high SVCV spleenoproliferative responses in mice and the development of antibodies to both fused proteins. These results indicate the functionality of the constructs and the possibility of giving protection in fish.